Systematic review on techniques for the creation of pneumoperitoneum in laparoscopic surgeries - Asna Zehra Naqvi; Vignesh Balasubaramaniam; Wasif Raza; Lajpat Rai; Graham S Whiteley (Asian Journal of Medical Sciences, 2024)
Recently, laparoscopic surgeries (LPSs) are becoming increasingly prevalent. Incorporating these methods into clinical practice necessitates an in-depth understanding of the surgical techniques and multifaceted instrumentation that are specific to a slightly invasive operation. Within this systematic review, attention is directed to the technique for pneumoperitoneum creation, like the open and closed technique, to select optimal procedures along with appropriate utilization, with prominence on complication avoidance. This systematic literature review (SLR) examined significant findings from 2018 to 2023. This SLR complies with the quality standards suggested by the PRISMA document. Web of Science, SCOPUS, ProQuest, ScienceDirect, and SpringerLink are the resources. The exclusion criteria included case reports, abstracts, and letters, as well as inclusion criteria included randomized, quasi-randomized, non-randomized, and cohort investigations on human patients, provided that they liked access safety methods and presented values. According to the findings, it can be concluded that the LP inspection of the abdominal cavity (AC), which necessitates cannula implantation, is safe and effective. Closed (Veress needle technique) and open (Hasson technique) pneumoperitoneum induction techniques are frequently utilized. Most laparoscopy (LP) surgeons prefer closed LP utilizing a Veress needle and the first trocar’s masked insertion. Critics of the Veress needle, however, assert that this technique increases the risk of vascular injury. According to proponents of the open Hasson technique, vascular injury could be entirely avoided. The use of an open approach utilizing a blunt-tipped trocar for the formation of pneumoperitoneum may provide a potentially safer alternative during LPSs, depending on safety considerations.